2022
DOI: 10.3390/diagnostics12030560
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gestational Ovarian Choriocarcinoma: A Rare Ovarian Cancer Subtype

Abstract: Non-Gestational Ovarian Choriocarcinoma (NGOC) is an extremely rare ovarian tumor, with an incidence of less than 0.6% of malignant ovarian germ cell tumors. Its close pathologic resemblance to Gestational Ovarian Choriocarcinoma (GOC), however, requires special attention as the treatments differ greatly. NGOC typically affects patients in late adolescence or early reproductive years. As a result, NGOCs are often misdiagnosed as ectopic pregnancies due to their common presentation of bleeding, abdominal pain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
5
0
4
Order By: Relevance
“…It is unrelated to pregnancy and was reported to have primary sites in the ovaries, lungs, cervix, endometrium, breast, bladder, and gastrointestinal tract ( 9 ). Due to the similarities in clinical and histological features, the differentiation between these two types can only be achieved by genetic testing which identifies the presence of paternal DNA in gestational choriocarcinoma ( 12 ). In the case of our patient, it remains unclear whether choriocarcinoma derived from her previous pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is unrelated to pregnancy and was reported to have primary sites in the ovaries, lungs, cervix, endometrium, breast, bladder, and gastrointestinal tract ( 9 ). Due to the similarities in clinical and histological features, the differentiation between these two types can only be achieved by genetic testing which identifies the presence of paternal DNA in gestational choriocarcinoma ( 12 ). In the case of our patient, it remains unclear whether choriocarcinoma derived from her previous pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reproductive history plays an important role in distinguishing NGOC from OC. Cronin et al [ 5 ] have suggested that a diagnosis of NGOC is supported by the lack of sexual intercourse or pregnancy in the history. However, this postmenopausal patient had experienced a normal vaginal delivery and four abortions.…”
Section: Discussionmentioning
confidence: 99%
“…The level of β-hCG can help exclude the possibility of an ectopic pregnancy, in which the level is rarely higher than 100000 mIU/mL. In contrast, the β-hCG level in NGOC is commonly 10–100 times higher[ 5 ]. In our report, the postmenopausal woman presented with vaginal bleeding, an abdominal mass, and a sharply elevated serum β-hCG level at 214405.5 mIU/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Non-gestational trophoblastic tumors are extremely rare and unrelated to pregnancy, and DNA analysis demonstrates the absence of any paternal genes. 6 It has been hypothesized that the retained primordial germ cells may migrate abnormally during embryonic development into the different locations and develop into nongestational trophoblastic tumors. 7 Most of the GTDs are associated with gestational events and occur in the female genital tract.…”
Section: Abstract Cystic Lung Lesions Diffuse Lung Disease Lung Cysts...mentioning
confidence: 99%